Antimutagenic effect of Agaricus blazei Murrill mushroom on the genotoxicity induced by cyclophosphamide - Delmanto, R. D.; de Lima, PLA; Sugui, M. M.; da Eira, A. F.; Salvadori, Daisy Maria Favero [UNESP]; Speit, G.; Ribeiro, L. R. (Elsevier B.V., 2001)
Agaricus blazei Murrill extracts have previously been shown to have anticarcinogenic and antimutagenic proper-ties. These results suggest that antimutagenic activity, besides the modulation of the immune system, might be involved in the anticarcinogenic action of A. blazei. To investigate the possible antimutagenic effect of A. blazei in vivo, we evaluated its effect on clastogenicity induced by cyclophosphamide (CP) in mice, using the micronucleus test in bone marrow (MNPCE) and in peripheral blood (MNRET). Male Swiss mice were treated with CP (25 or 50 mg/kg i.p.) or with CP plus mushroom solution at three different temperatures: 4, 21, and 60 degreesC. Aqueous solution of a mixture from various lineages of the mushroom inhibited induction of micronuclei by CP in bone marrow and in peripheral blood of mice. In contrast to the mixture of lineages, a single isolated lineage did not lead to a reduction of CP-induced MN frequencies in either bone marrow or blood cells of mice. The results suggest that under certain circumstances these mushrooms exhibit antimutagenic activities that might contribute to an anticarcinogenic effect. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: antimutagenicity; Agaricus blazei Murrill; micronucleus test; cyclophosphamide